RESEARCH EFFICIENCY OPTICAL TRANSPORT NETWORKS WITH USE TRANSFERRING AND RECEPTION OPTOELECTRONICS MODULE - Hasanov, Mehman H.; Ibrahimov, Bayram G.; Qodjaeva, Shalala F. (International Journal of Research -GRANTHAALAYAH, 2018)
The analyses qualities functioning optical transport communication networks on the basis technology spectral divisions of the channels using transferring and reception optoelectronics of the module. On a basis research the method improvement indicators fiber-optical systems transfer information is offered and key parameters efficiency and a noise stability optical transport networks are defined.